The Role of Leverage, Company Size and Retention Ratio on Banking Companies Value in Indonesia - Permata Sari, Anggi; Kadarningsih, Ana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of leverage, company size and retention ratio on company value in banking companies listed on the Indonesian Stock Exchange during the 2020-2023 period. The population taken and used in this research is annual data from 45 companies for four (4) periods totaling 180 data. This research uses the Eviews 12 analysis tool. Applying the Multiple Regression Analysis research method with the data type in the form of panel data with a Fixed Effect Model. The results of this company value research show that leverage and company size have a significant effect on company value, while the retention ratio has an insignificant effect on company value.